Nurses’ experiences in implementing Nurse Initiated Management of Anti-Retroviral Therapy (NIMART) in primary health care facilities in Dr Ruth Segomotsi Mompati District, North West Province - Sibisi, Nthabiseng (My University, 2024)
Aim of study- This study aimed to explore the nurses’ experiences in the implementation of NIMART in Dr Ruth Segomotsi Mompati District since its inception in 2010 to 2017. Methods This study employed an exploratory qualitative research design. The study setting included nine PHC facilities in three sub-districts. The study included only those nurses who had been trained to implement the NIMART in the district PHC facilities from 2010-2017. The final sample included Sixteen (16) nurses, comprising of three males and thirteen females from the three eight-hour operational clinics and six 24-hour Community Health Centres (CHCs). Data were therefore collected using in-depth interviews lasting thirty-five minutes (minimum) one and half hours 1h30 minutes (maximum). These interviews were guided by a semistructured interview guide. Data were later transcribed verbatim using an electronic software O’ Transcribe, and then analysed using MAXQDA 2018v, where inductive coding was applied. Thematic analysis was employed to interpret and represent data, which was finally presented as themes based on participants’ dominant narratives. Results- There were five key themes that emerged from this study. These included: perceptions about the NIMART programme mostly related to it being a task-shifting strategy when managing HIV and Aids and the programme benefits; contextual elements affecting access and adherence to NIMART, and challenges such as socio-cultural factors, social norms, socio-political and governance factors; facilitators of NIMART implementation in terms of functional health information management system and clinical guidelines, multidisciplinary team and skilled personnel, impactful counselling services, and intrinsic nurse motivators. Challenges of NIMART implementation included insufficient human resources for health, services integration, poor management and health-service support systems, lack of capacity building, ART unavailability and poor patient compliance to ART, and nurse demotivation. The proposed interventions by the nurses included provision of training, increasing staff to curb workload, management support, and debriefing, health service support resources and patient support improvement. Conclusion Task-shifting and successful NIMART implementation are complex notions, which can be successful if accompanied by training, reorganisation of services, mentoring, supervision, and ongoing support from existing health-service system structures. The rural health context must be considered as unique, and policies should be tailored to suit the needs of rural healthcare workers and patients. Dr RSM case-study has shows the plight of farm labourers and the need for a multisectoral approach to address patient related issues in this context. The challenges to successful NIMART implementation suggest a need for reorientation of health-services to fit rural contexts.
A research report submitted in partial fulfilment of the requirement for the degree of Masters of Public Health to the Faculty of Health Sciences, University of the Witwatersrand, School of Public Health, Johannesburg, 2023
Keywords: Antiretroviral Therapy; Nurses; Rural health; SDG-4: Quality education; SDG-16: Peace, justice and strong institutions